(untitled) (Bulletin of Innovative Research, 2026)
This article investigates the application of probiotics and enzymes in modern dairy technology. The study shows that dairy products enriched with Lactobacillus and Bifidobacterium strains enhance the organoleptic quality, texture, and probiotic activity of cheese and yogurt. Enzymes (rennin, lipase, lactase) help stabilize acidity and optimize the fermentation process. During storage, probiotic counts remain relatively stable, preserving the functional properties of the products.